Is there evidence for the suggestion that fatigue accumulates following resistance exercise? - Kataoka, R.; Vasenina, E.; Hammert, W. B.; Ibrahim, A. H.; Dankel, S. J.; Buckner, S. L. (Sports Medicine, 2022)
It has been suggested that improper post-exercise recovery or improper sequence of training may result in an `accumulation` of fatigue. Despite this suggestion, there is a lack of clarity regarding which physiological mechanisms may be proposed to contribute to fatigue accumulation. The present paper explores the time course of the changes in various fatigue-related measures in order to understand how they may accumulate or lessen over time following an exercise bout or in the context of an exercise program. Regarding peripheral fatigue, the depletion of energy substrates and accumulation of metabolic byproducts has been demonstrated to occur following an acute bout of resistance training; however, peripheral accumulation and depletion appear unlikely candidates to accumulate over time. A number of mechanisms may contribute to the development of central fatigue, postulating the need for prolonged periods of recovery; however, a time course is difficult to determine and is dependent on which measurement is examined. In addition, it has not been demonstrated that central fatigue measures accumulate over time. A potential candidate that may be interpreted as accumulated fatigue is muscle damage, which shares similar characteristics (i.e., prolonged strength loss). Due to the delayed appearance of muscle damage, it may be interpreted as accumulated fatigue. Overall, evidence for the presence of fatigue accumulation with resistance training is equivocal, making it difficult to draw the conclusion that fatigue accumulates. Considerable work remains as to whether fatigue can accumulate over time. Future studies are warranted to elucidate potential mechanisms underlying the concept of fatigue accumulation.